[Posters from Olympic sponsors and supporters] [AMP, Ansett, BHP, Coca Cola, Fairfax, Fosters, IBM, Kodak, Lindemans, NIKE, Telstra, Traveland, Visa, Westpac]. (1996)
Majority portray athletes in action in their respective sports with sponsors' logos and sayings. Some sponsors may have a series of posters.
[POSTER 2022-4038] Bring on the world : Ansett introduces the Sydney 2000 official airline team -- [POSTER 2022-4039 - 4043] Traveland : official travel agent of the Sydney 2000 Olympic Games -- [POSTER 2022-4044] [Ansett Australia showing special Sydney 2000 Jumbo 737 VH-HYN jet flying over Uluru with the livery of the Olympic Torch Relay] -- [POSTER 2022-4045] The Sydney Olympic Games : IBM -- [POSTER 2022-4046] Backing Australia’s Olympians with every drop on Earth -- [POSTER 2022-4047] [Ansett Australia showing special Sydney 2000 B747-400 Jumbo jet flying over Sydney].
Keywords: Sports sponsorship -- Australia -- Posters; Business enterprises -- Australia -- Posters